2012
DOI: 10.1111/j.1467-789x.2011.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol is a protective factor for non‐alcoholic fatty liver disease in healthy men

Abstract: Visceral fat is a risk factor for non-alcoholic fatty liver disease (NAFLD). A reduction in sex hormones is associated with increased abdominal fat. Thus, we investigated whether reduced testosterone (T) or oestradiol (E2) levels in men are associated with NAFLD and central obesity. The study involved a survey of 1,882 men between 20 and 60 years of age. We detected hepatic fat infiltration by ultrasound. Early morning serum was analyzed for total testosterone (TT), E2, sex hormone-binding globulin (SHBG), fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 44 publications
3
63
2
Order By: Relevance
“…No associations studies for fatty liver with estradiol or testosterone have been reported in US population based studies. One study in China found that was E2 associated with lower fatty liver prevalence in men, 37 however our study shows a strong opposite association. One Korean study found that lower levels of testosterone in men were associated with NAFLD.…”
Section: Discussioncontrasting
confidence: 90%
“…No associations studies for fatty liver with estradiol or testosterone have been reported in US population based studies. One study in China found that was E2 associated with lower fatty liver prevalence in men, 37 however our study shows a strong opposite association. One Korean study found that lower levels of testosterone in men were associated with NAFLD.…”
Section: Discussioncontrasting
confidence: 90%
“…Several studies showed that menopause is associated with NAFLD [15][16][17]. The increase in prevalence of NAFLD following menopause implies that estrogen may have protective effects against NAFLD and/or its associated risk factors [17,19,27]. The NHANES study also demonstrated that the prevalence of NAFLD is higher in postmenopausal women compared with premenopausal women (odds ratio 2.05, 95% CI: 1.43-2.94) [15].…”
Section: Commentsmentioning
confidence: 90%
“…In a large crosssectional study in men, low E 2 was associated with the presence of hepatic steatosis (48). Furthermore, tamoxifen when used as an adjuvant chemotherapeutic agent in patients with breast cancer is known to be associated with NAFLD (49).…”
Section: Oestrogensmentioning
confidence: 99%